A novel proposal [large type] - Hunter, Denise, 1968- (Center Point Large Print, 2023)
"When western novelist Sadie Goodwin must pen a romance novel to rescue her lackluster sales, there's only one tiny problem: she's never been in love. Desperate to salvage her career, Sadie accepts an invitation to hole up at her friend's beach duplex for the summer and devote herself to this confounding genre. After all, where better to witness love than on the beautiful South Carolina shore? But Sadie soon finds many ways to procrastinate the dreaded task -- like getting to know the beach regulars and installing a Little Free Library on the property. She even attempts conversations with Sam Ford, the frustratingly stubborn neighbor on the other side of the duplex. But things take an unexpected turn when Sadie finds inside her library an abandoned novel with a secret compartment -- and a beautiful engagement ring tucked inside. Suddenly, locating the ring's owner becomes the perfect way to put off writing that romance. Sadie draws a reluctant Sam into her mission. And as the two close in on an answer to the mysterious proposal, she discovers a tender side to him. She begins to wonder if he just might make the perfect hero for her romance novel -- or maybe even her heart."--